Mindfulness Practices in Psychological Wellbeing - Jessica Cendana; Heru Suherman; Ponijan Ponijan (CV. Rayyan Dwi Bharata, 2024)
The aim of this research is to explore previous studies on the practice of Mindfulness in Self-Wellbeing. One influential factor in psychological well-being is mindfulness (Krego et al., 2019). This research adopts a literature study approach. In conclusion, the understanding of uncertainty, interventions such as meditation, factors supporting psychological well-being, and the literature study approach provide valuable insights to support the understanding and development of individual psychological well-being in the face of life's uncertainties